OR01-03 Thyroid Receptor Alpha Interacts with COUP-TFII in the Regulation of Postnatal Skeletal Muscle Regeneration - Aguiari, Paola (J Endocr Soc, 2020)
Myopathic changes, including muscular dystrophy and weakness, are commonly described in hypothyroid and hyperthyroid patients. Thyroid hormone signaling, via activation of thyroid nuclear receptors (TRs), plays an essential role in the maintenance of muscle mass, function, and regeneration. TRs are ligand-inducible transcription factors expressed in almost all tissues, including skeletal muscle. In a mouse model of Resistance to Thyroid Hormone carrying a frame-shift mutation in the TRα gene (TRα1PV)(1,2) we observed skeletal muscle loss with aging and impaired skeletal muscle regeneration after injury. We recently described that TRα interacts with the nuclear orphan receptor Chicken Ovalbumin Upstream Promoter-factor II (COUP-TFII, or NR2F2), which is known to regulate myogenesis negatively and has a role in Duchenne-like Muscular Dystrophies(3). We showed that COUP-TFII expression declines with age in WT mice, while the skeletal muscle of TRα1PV mice shows a sustained significantly higher expression of COUP-TFII. Our findings suggest that the TRα/COUP-TFII interaction might mediate the impaired skeletal muscle phenotype observed in TRα1PV mice. To better characterize this interaction, we isolated SC from 10 months old WT and TRα1PV mice and cultured them in vitro using novel methods established within our lab. Using siRNA probes, we next silenced COUP-TFII and characterized the cells via RNA-seq analysis. In vitro, we assessed myoblast differentiation and proliferation using differentiation assays and EdU incorporation. We observed that satellite cells from TRα1PV mice display impaired myoblast proliferation and in vitro myogenic differentiation compared to WT SCs. However, when COUP-TFII was silenced, the myogenic potential of TRα1PV satellite cells was restored, with a higher proliferation of myoblasts and a higher number of fully differentiated myotubes after 4 days of myogenic induction. RNAseq analysis on satellite cells from TRα1PV mice after COUP-TFII knockdown showed upregulation of genes involved in the myogenic pathway, such as Myod1 and Pax7, and of genes in the thyroid hormone signaling, such as Dio2. Ingenuity Pathway Analysis further showed activation of pathways regarding cell growth, differentiation, matrix remodeling along with muscle function, muscle contractility, and muscle contraction. These in vitro results suggest that by silencing COUP-TFII we promote the myogenic pathway and may further rescue the impaired phenotype of TRα1PV mice. These studies can help increase our knowledge of the mechanisms involved in thyroid hormone signaling in skeletal muscle regeneration, which will ultimately increase the possibility of designing more specific treatments for patients with thyroid hormone-induced myopathies. References: (1)Milanesi, A., et al, Endocrinology 2016; (2)Kaneshige, M. et al, Proc Natl Acad Sci U S 2001; (3)Lee HJ, et al, Sci Rep. 2017.